Cytotoxicity of zinc nanoparticles biosynthesized by microorganisms on human keratinocyte cell line - Lopez Venditti, Eliana Daniela (2019)
Metal nanoparticles -NPs- (10-100 nm) have an important antimicrobial activity which suggests possible biomedical applications. Zinc NPs (ZnNPs) are widely used for different products. The aim of this work was to investigate the toxicity of ZnNPs biosynthesized by microorganisms, in a human keratinocyte cell line (HaCaT). ZnNPs were synthesized using Pseudomonas aeruginosa (ATCC 27853) and were characterized by UV-Vis spectroscopy and by transmission electron microscopy. HaCaT cells were incubated for 4 h and 24 h at different ZnNPs dilutions (1/2, 1/5 and 1/10). RPMI 1640 culture medium with 5% FBS, a metal precursor salt solution of ZnSO4 (0.1 and 0.25 mM), and a bacterial growth control of biosynthesis (BGC), were used as controls. Cell viability was evaluated by MTT assay, crystal violet and neutral red tests; reactive oxygen species (ROS) were studied by DCF-DA; superoxide dismutase (SOD) activity was determined by riboflavin-NBT method; and reduced glutathione (GSH) by Ellman reactive. ZnNPs cell capture assays were performed by fluorescence microscopy and changes in cell migration were evaluated by wound healing assay. As determined by fluorescence microscopy ZnNPs were able to enter HaCaT cells. The toxicity assays indicated that cell viability was significantly altered by ZnNPs 1/2 and BGC conditions after 4 h and 24 h incubation. ROS levels increased after 4 h incubation with ZnNPs 1/2, 1/5, and BGC, while a 24 h incubation, 1/10 dilution also augmented ROS. SOD activity increases at all ZnNPs dilutions tested, and with BGC. GSH was not modified by any treatment. Finally, the presence of ZnNPs and BGC in the culture media affected cell migration. Altogether these results suggest that ZnNPs are able not only to enter into skin cells but also to modify human keratinocyte viability, oxidant/antioxidant cell balance and cell migration. More studies are needed to unravel the mechanisms underlying these alterations.